Association of Polymorphisms in Inflammatory Cytokines Encoding Genes With Anti-N-methyl-D-Aspartate Receptor Encephalitis in the Southern Han Chinese - Li, Xing; Zhu, Jiajia; Peng, Yu; Guan, Hongbing; Chen, Jinyu; Wang, Zhanhang; Zheng, Dong; Cheng, Nan; Wang, Honghao (Frontiers in Neurology, 2020)
Background: Single nucleotide polymorphisms (SNPs) that occur within genes encoding inflammatory cytokines can result in quantitative or qualitative changes in their expression or functionality, potentially leading to the development of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. This study sought to evaluate the relationship between SNPs in inflammatory cytokines genes and the incidence of anti-NMDAR encephalitis in the Southern Han Chinese. Methods: In total, we enrolled 107 patients with anti-NMDAR encephalitis as well as 202 inpatient controls. Genotyping determination of all 309 patients was conducted for the IL-1β rs16944, IL-4 rs2243250, IL-4 rs2070874, IL-6 rs1800796, IL-10 rs1800872 and IL-17 rs2275913 genes. Results: The absence of G allele in IL-1β rs16944 SNP increased the risk of anti-NMDAR encephalitis (p = 0.017). Also, the frequencies of IL-1β, IL-4, IL-6, IL-10 and IL-17 were not associated with the disease (p > 0.05). Conclusions: We found that patients with anti-NMDAR encephalitis exhibit a distinct immunological profile, and we found that patients carrying certain cytokine-related SNPs may be at risk of more severe outcomes associated with this condition. The absence of G allele in IL-1β rs16944 may increase susceptibility to anti-NMDAR encephalitis in the Southern Han Chinese.